Cardiolipin-Mediated Mitochondrial Dynamics and Stress Response in Arabidopsis - Pan, Ronghui (American Society of Plant Biologists, 2014)
Mitochondria are essential and dynamic organelles in eukaryotes. Cardiolipin (CL) is a key phospholipid in mitochondrial membranes, playing important roles in maintaining the functional integrity and dynamics of mitochondria in animals and yeasts. However, CL’s role in plants is just beginning to be elucidated. In this study, we used Arabidopsis thaliana to examine the subcellular distribution of CL and CARDIOLIPIN SYNTHASE (CLS) and analyzed loss-of-function cls mutants for defects in mitochondrial morphogenesis and stress response. We show that CL localizes to mitochondria and is enriched at specific domains, and CLS targets to the inner membrane of mitochondria with its C terminus in the intermembrane space. Furthermore, cls mutants exhibit significantly impaired growth as well as altered structural integrity and morphogenesis of mitochondria. In contrast to animals and yeasts, in which CL’s effect on mitochondrial fusion is more profound, Arabidopsis CL plays a dominant role in mitochondrial fission and exerts this function, at least in part, through stabilizing the protein complex of the major mitochondrial fission factor, DYNAMIN-RELATED PROTEIN3. CL also plays a role in plant responses to heat and extended darkness, stresses that induce programmed cell death. Our study has uncovered conserved and plant-specific aspects of CL biology in mitochondrial dynamics and the organism response to environmental stresses.